AQCQ-Functional Equation in Non-Archimedean Normed Spaces - M. Eshaghi Gordji; R. Khodabakhsh; S.-M. Jung; H. Khodaei (Abstract and Applied Analysis)
We prove the generalized Hyers-Ulam stability of generalized mixed type of quartic, cubic, quadratic and additive functional equation in non-Archimedean spaces.